Anti-hyperuricemic and neuroprotective effects of Populus nigra L. (Saliacaceae) flower buds used in Algerian folk medicine - Nadjet Debbache-Benaida; Meriem Berboucha; Karima Ayouni; Dina Atmani; Cheraft Nassima; Hania Boudaoud; Noureddine Djebli; Djebbar Atmani (GarVal Editorial Ltda., 2018)
Context: Populus nigra L., is a species of cottonwood poplar that belongs to the Salicaceae family, is cultivated in multiple areas in Algeria, with an Algerian name of Safsaf. Aims: To evaluate the Populus nigra flower buds extract for its effects on brain modifications against aluminum-induced neurotoxicity in mice. The hypouricemic action of the extract was also evaluated. Methods: To evaluate the effect of extract on AlCl3-induced neurotoxicity on mice a battery of tests was performed to assess a spectrum of learning and memory functions. The hypouricemic action of the extract was studied by the measure of uric acid levels and liver xanthine oxidoreductase activity in normal and hyperuricemic mice. Results: Co-administration of P. nigra extract (200 mg/kg) and AlCl3 (100 mg/kg/day) combined with D-galactose (200 mg/kg/day) during four weeks was found to antagonize the harmful effects of AlCl3 by restoring all the test parameters. Moreover, extract restored the pyramidal cells to near normal in cerebral cortex of mice. Extract, when administered three times orally to the normal and oxonate-induced hyperuricemic mice, was able to elicit significantly hypouricemic effect comparable to that of allopurinol. Conclusions: P. nigra flower buds extract can be considered as food enabling to antagonize AlCl3 toxicity and to control serum uric acid levels.